Tradisi Literasi Budaya Pesantren di Pondok Pesantren Gedangan Kadungdung Sampang - Wadud, Abdul; Chairiyah, Chairiyah (Ideas Publishing, 2024)
This research highlights the importance of cultural literacy traditions in shaping the character and personality of santri. The aim of this research is to analyze cultural literacy in Gedangan Islamic boarding schools. Islamic boarding schools are known for their cultural background of high literacy in the study of classical books. This research method uses qualitative which can explain literacy. The qualitative method used is descriptive by obtaining data from interviews, observation and documentation. The result of literacy that occurs at the Gedangan Islamic boarding school is a love of religious knowledge, example, togetherness, discipline, independence, sincerity and simplicity.